(untitled) (Kampelmas, 2024)
According to the Program for International Student Assessment (PISA), Indonesia ranked 74th out of 79 countries in the field of children’s literacy in 2018. Seeing this reality, it is the community’s obligation as a partner in the national education component to participate in raising mutual awareness regarding the literacy abilities of the next generation. nation. Therefore, Giat Literacy, which is basically an assessment to measure literacy levels based on AKM and PISA indicators, can be used as a solution to overcome this problem, especially in Grenggeng Village. The stages carried out in Literacy Activities include planning, preparing activity proposals, outreach, and implementation. The results of the research show that the development of a literacy culture can increase the enjoyment, interest, and interest in reading.